Low-cost descriptors of electrostatic and electronic contributions to anion redox activity in batteries. (21st July 2020) - Davies, Daniel W; Morgan, Benjamin J; Scanlon, David O; Walsh, Aron
Abstract: Conventional battery cathodes are limited by the redox capacity of the transition metal components. For example, the delithiation of LiCoO2 involves the formal oxidation from Co(III) to Co(IV). Enhanced capacities can be achieved if the anion also contributes to reversible oxidation. The origins of redox activity in crystals are difficult to quantify from experimental measurements or first-principles materials modelling. We present practical procedures to describe the electrostatic (Madelung potential) and electronic (integrated density of states) contributions, which are applied to the Li M O2 and Li2 M O3 ( M  = Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Hf, Ta, W, Re, Os, Ir, Pt, Au) model systems. We discuss how such descriptors could be integrated in a materials design workflow.